Exosomes derived from human embryonic mesenchymal stem cells promote osteochondral regeneration. Issue 12 (December 2016) - Zhang, S.; Chu, W.C.; Lai, R.C.; Lim, S.K.; Hui, J.H.P.; Toh, W.S.
Summary: Objective: Clinical and animal studies have demonstrated the efficacy of mesenchymal stem cell (MSC) therapies in cartilage repair. As the efficacy of many MSC-based therapies has been attributed to paracrine secretion, particularly extracellular vesicles/exosomes, we determine here if weekly intra-articular injections of human embryonic MSC-derived exosomes would repair and regenerate osteochondral defects in a rat model. Methods: In this study, osteochondral defects were created on the trochlear grooves of both distal femurs in 12 adult rats. In each animal, one defect was treated with 100 μg exosomes and the contralateral defect treated with phosphate buffered saline (PBS). Intra-articular injections of exosomes or PBS were administered after surgery and thereafter weekly for a period of 12 weeks. Three unoperated age-matched animals served as native controls. Analyses were performed by histology, immunohistochemistry, and scoring at 6 and 12 weeks after surgery. Results: Generally, exosome-treated defects showed enhanced gross appearance and improved histological scores than the contralateral PBS-treated defects. By 12 weeks, exosome-treated defects displayed complete restoration of cartilage and subchondral bone with characteristic features including a hyaline cartilage with good surface regularity, complete bonding to adjacent cartilage, and extracellular matrix deposition that closely resemble that of age-matched unoperated control. In contrast, there were only fibrous repair tissues found in the contralateral PBS-treated defects. Conclusion: This study demonstrates for the first time the efficacy of human embryonic MSC exosomes in cartilage repair, and the utility of MSC exosomes as a ready-to-use and 'cell-free' therapeutic alternative to cell-based MSC therapy.